CGIAR Evaluation Framework - CGIAR Advisory Services Shared Secretariat (CGIAR Advisory Services, 2022)
The new CGIAR Evaluation Framework was approved by the CGIAR System Board in February 2022 and endorsed by the System Council, the CGIAR strategic decision-making body, that took place on 8-9 March 2022.